Speech Training through Interactive Web: Say it Right: Teaching Prosodic Features - Kaushik, Dr. Sharda (International Journal of Psychosocial Rehabilitation, 2020)
An average learner of English in India acquires speaking skills through exposure to different varieties of English used in their surroundings. Almost all varieties of Spoken English (SE) carry slight to heavy influence of vernacular dialects or languages. Such influences cause varied degrees of unintelligibility among speakers, amidst which global intelligibility becomes a distant dream. Speech, largely resulting from habit formation, is difficult to change. However, learners’ proficiency in SE can be enhanced with intervention made using technology. Technology provides effective learning tools in a variety of formats. Those using it will be able to interact with model speech samples. Technology has an inherent quality of inducing interest value in learning programs thereby triggering motivation in learners who then begin to participate proactively in learning. The present research focuses on teaching prosodic features of English to teacher trainees who develop motivation to learn their use due to inclusion of technological tools by participating in a specifically designed course.